2014
DOI: 10.1371/journal.pone.0100771
|View full text |Cite
|
Sign up to set email alerts
|

Raised Trappin2/elafin Protein in Cervico-Vaginal Fluid Is a Potential Predictor of Cervical Shortening and Spontaneous Preterm Birth

Abstract: Early spontaneous preterm birth is associated with inflammation/infection and shortening of the cervix. We hypothesised that cervico-vaginal production of trappin2/elafin (peptidase inhibitor 3) and cathelicidin antimicrobial peptide (cathelicidin), key components of the innate immune system, are altered in women who have a spontaneous preterm birth. The aim was to determine the relationship between cervico-vaginal fluid (CVF) trappin2/elafin and cathelicidin protein concentrations with cervical length in woma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…To date, there is evidence that both term and preterm labor are linked to an inflammatory process, and over the last few decades several biomarkers, including inflammatory cytokines, have been investigated for the prediction of PTB. Recently, Abbot et al . have shown that inflammation anticipates cervical shortening, thus questioning the utility of CL screening in asymptomatic women.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is evidence that both term and preterm labor are linked to an inflammatory process, and over the last few decades several biomarkers, including inflammatory cytokines, have been investigated for the prediction of PTB. Recently, Abbot et al . have shown that inflammation anticipates cervical shortening, thus questioning the utility of CL screening in asymptomatic women.…”
Section: Discussionmentioning
confidence: 99%
“…However, high levels of these mediators in CVL have been previously associated with adverse pregnancy outcomes such as cervical shortening and preterm birth suggesting that the concentrations we found were indicative of a response to some stimulus in vivo . 31,32 …”
Section: Commentmentioning
confidence: 99%
“…13,14,17,18 More recent efforts have focused on biomarkers such as pregnancy-associated plasma protein A, fetal fibronectin, and placental growth factor to augment the predictive capacity of demographic and clinical risk factors; however, this body of research has not yet yielded a clear approach for implementation in clinical practice. [19][20][21][22] As with prior studies, important risk factors in our model included race and obstetric history. Our inclusion of childhood abuse in the model is also consistent with recent literature demonstrating the importance of childhood history as a significant risk factor.…”
Section: Figmentioning
confidence: 99%
“…[13][14][15] More recently, risk models including cervical length as well as various biomarkers have shown promise in increasing prognostic performance. [16][17][18][19][20][21][22] However, this research has not yet yielded a risk assessment tool for use in clinical practice; moreover, the majority of these prediction models have been derived using a general population, which may overinflate their ability to discriminate risk within an a priori at-risk population of Medicaid recipients.…”
Section: Introductionmentioning
confidence: 99%